Selections from Franciscan Notes - Williamson, Alan (Christianity & literature, 2018)
Three poems by Alan Williamson are presented. "Upper Church." First Line: Let the notes begin, and the blue: Last Line: our model of transparence toward all that is. "Lower Church." First Line: Dread advances. Wedded to stone. Last Line: Twice, conquering, I've crossed over. "Blessing of the Animals." First Line: Oh you who preached to the double orchestra; Last Line: making the sign of the Cross.)